2010
DOI: 10.1111/j.1463-5224.2010.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Tear production in normal juvenile dogs

Abstract: Age, weight, and gender significantly affect tear production in normal juvenile dogs. STT1 increases to adult values at approximately 9-10 weeks of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
30
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 17 publications
8
30
4
Order By: Relevance
“…In dogs, there was a decrease of 0.4 mm seen for each year of life (Hartley et al 2006). Lacrimal production was significantly altered based on age, weight and sex in dogs, and after nine-to-ten weeks of age, there was an increase of 0.15mm/min for each day of life of the animal and of 0.84 mm/min for each kilogram of weight (Broadwater et al 2010). To avoid external influences on the results and discordance with what has been reported in the literature (Hartley et al 2006), a single lot of STT was used to prevent alterations in the absorption and porosity of the paper.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In dogs, there was a decrease of 0.4 mm seen for each year of life (Hartley et al 2006). Lacrimal production was significantly altered based on age, weight and sex in dogs, and after nine-to-ten weeks of age, there was an increase of 0.15mm/min for each day of life of the animal and of 0.84 mm/min for each kilogram of weight (Broadwater et al 2010). To avoid external influences on the results and discordance with what has been reported in the literature (Hartley et al 2006), a single lot of STT was used to prevent alterations in the absorption and porosity of the paper.…”
Section: Discussionmentioning
confidence: 94%
“…Dogs maintained in left-side position did not present alterations in IOP levels in either eye (Honsho et al 2004), however another study demonstrated a 2-3 mmHg difference in the IOP value depending on the decubitus studied (dorsal, ventral, seated) (Broadwater et al 2010). Furthermore, the authors relate the importance of maintaining the animals in the same position prior to measuring IOP and always using the same position to annul the effects that body position may have on the obtained results (Broadwater et al 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study, Broadwater et al. , 14 discussed that gender significantly affected both STT I and II values in dogs. The authors stated that STTs in males were significantly higher than females.…”
Section: Discussionmentioning
confidence: 96%
“…The lipid layer produced by the meibomian gland stabilizes the tear film, preventing evaporation, and goblet cells in the palpebral conjunctiva elaborate mucin, which allows the aqueous tear fluid to spread evenly over the cornea. 1 Simultaneous dysfunction in the lacrimal and nictitating membrane glands causes keratoconjunctivitis sicca (KCS) disorder. KCS is caused by a pathological reduction in the aqueous component of the tear film and defined as an Schirmer tear test (STT) value <10 mm/min and concomitant ocular surface pathological changes or lesions or something besides pathology.…”
mentioning
confidence: 99%